Comparison of Eurofit Test Results of 11-17-Year- Old Male and Female Students in Kosovo - Berisha, Milaim; Cilli, Murat (European Scientific Journal, ESJ, 2017)
This study aims to compare EuroFit test results of 11-17-year-old males and females in Kosovo. 742 students were included in the study. 347 females and 395 males were determined by random selection from the schools in urban and rural areas of all regions. Kosovo’s general population rate (52% male 48% female) was considered when determining the proportion of male and female students. Anthropometric characteristics including height, weight, and Body Mass Index (BMI) of students and the motoric characteristics including the values obtained from the tests such as flamingo balance, plate tapping, sit and reach, standing broad jump, handgrip strength, sit-ups (30 sec), bent arm hang, 10x5m shuttle run and 20 m endurance were compared. As a result, there was no statistically significant difference between the anthropometric characteristics of male and female students in adolescence; however, it was observed that as the age increased, males became heavier and taller than females (p<0.05). In general, while there was no statistically significant difference between males and females in flamingo balance, plate tapping and sit and reach tests (p> 0.05), males were determined to be more successful than females in standing broad jump test, handgrip strength test, sit-ups (30 sec) and 20 m endurance tests (p<0.05). It is observed that students in Kosovo are more successful than the other countries regarding motoric tests such as the anthropometric characteristics, which are thought to be more related to genetics, and speed/agility of arms and legs. On the other hand, they are unsuccessful in comparison with other countries with regard to flexibility and endurance in tests which are thought to be influenced by factors such as lifestyle, nutrition, and training.